National Mission on Bamboo Technology and Trade Development - Planning Commission (Planning Commission, 2003)
The rapid increase in greenhouse gases in the atmosphere, land degradation, increasing floods and droughts, deforestation, loss of biodiversity and productivity are leading to an ecological crisis affecting livelihood options for development and increasing poverty, pollution and unsustainable development. As the poor ultimately bear the brunt of these adversities, scientific management and augmentation of natural resources has to be given highest priority in development.
Planning Commission Government of India
Planning Commission Government of India